An Exploratory Examination of the Effects of Workplace Strain on Correctional Officers. Issue 1 (2nd January 2023) - Abeyta, Stephen
ABSTRACT: This study uses data based on a random sample of correctional officers from eight different correctional facilities in the Northeast, to analyze strain, distress, and substance use through the lens of General Strain Theory (GST). This paper specifically seeks to establish correctional officers as a necessary component of mass incarceration research by explaining how their environment can lead to maladaptive behaviors. This is done by elaborating on how the environment of corrections institutions fosters various levels of distress in its employees, thereby leading to detrimental behavioral alterations such as substance use. Results indicate that higher levels of workplace strain either lead to substance use, or facilitate greater substance use, however this relationship is attenuated by occupational distress. This study shows that the very structure of the incarceration institution places workplace strain on employees which indirectly cause detrimental behavior augmentations.